Effects of Allium Hirtifolium Hydroalcoholic Extract and N-acetylcysteine on the Oxidative Toxic Stress Biomarkers in Aluminum Phosphide and Paraquat ‎Toxicity in Rats - Hassan Ghasemi; Seyed Mostafa Hosseini Zijoud; Nejat Khiripour; Omid Heidari Shayesteh; Amir Nili-Ahmadabadi; Akram Ranjbar* (Lorestan University of Medical Sciences, 2021)
Background and Aim: It has been indicated that aluminum phosphide (ALP) and paraquat (PQ) poisoning generate oxidative stress through the production of free radicals. The aim of the present study was to examine the effect of hydro alcoholic extract of Persian shallot and N-acetyl cysteine (NAC) against induced oxidative stress by PQ and ALP. Materials and Methods: Adult male Wister rats were divided into ten groups of 7. Animals received ALP and PQ alone and also in combination with NAC and the hydro alcoholic extract of Persian shallot. After twenty-four hours of treatment, the animals were scarified and their blood as well as liver samples were collected. Then, alanine aminotransferase (ALT), aspartate aminotransferase (AST), catalase (CAT) activity, as well as total antioxidant capacity (TAC) and lipid peroxidation (LPO) were measured. Results: The PQ and ALP significantly increased ALT and AST leakage compared to the control group (P<0.05). The TAC of serum and liver remarkably increased in the groups treated with NAC and hydro alcoholic extracts of Persian shallot in comparison with the control group (P < 0.05). Conclusion: As a natural antioxidant, the hydro alcoholic extract of Persian shallot can counteract with oxidative stress induced by ALP and PQ to ameliorate liver function. Keywords: Persian Shallot, Oxidative stress, N-acetyl cysteine, Aluminum Phosphide, Paraquat